Exploratory Factors Analysis of Employee Retention at Tertiary Educational Institution: A Case Study of a Private University in East Indonesia - Tansuria, Billy Ivan; Nelwan, Melinda Lydia (Bina Nusantara University, 2018)
This research aimed to identify the factors that contributed to the employee retention in the tertiary educational institution in Indonesia. The researchers used a case study of a private university in East Indonesia. This research was an exploratory factor analysis research. The items generated from in-depth interviews were developed into a questionnaire and distributed to 165 employees of the particular university based on purposive sampling method. About 105 respondents were obtained. The researchers utilized SPSS to analyze the data. The result shows that performance management function, organizational culture, employee engagement, social support, and work environment are the main factors contributing to the employee retention in the university. Among those factors, the performance management function is the factor with the highest factor loading.